Fire as a driver and mediator of predator–prey interactions. (23rd March 2022) - Doherty, Tim S.; Geary, William L.; Jolly, Chris J.; Macdonald, Kristina J.; Miritis, Vivianna; Watchorn, Darcy J.; Cherry, Michael J.; Conner, L. Mike; González, Tania Marisol; Legge, Sarah M.; Ritchie, Euan G.; Stawski, Clare; et al.
ABSTRACT: Both fire and predators have strong influences on the population dynamics and behaviour of animals, and the effects of predators may either be strengthened or weakened by fire. However, knowledge of how fire drives or mediates predator–prey interactions is fragmented and has not been synthesised. Here, we review and synthesise knowledge of how fire influences predator and prey behaviour and interactions. We develop a conceptual model based on predator–prey theory and empirical examples to address four key questions: ( i ) how and why do predators respond to fire; ( ii ) how and why does prey vulnerability change post‐fire; ( iii ) what mechanisms do prey use to reduce predation risk post‐fire; and ( iv ) what are the outcomes of predator–fire interactions for prey populations? We then discuss these findings in the context of wildlife conservation and ecosystem management before outlining priorities for future research. Fire‐induced changes in vegetation structure, resource availability, and animal behaviour influence predator–prey encounter rates, the amount of time prey are vulnerable during an encounter, and the conditional probability of prey death given an encounter. How a predator responds to fire depends on fire characteristics (e.g. season, severity), their hunting behaviour (ambush or pursuit predator), movement behaviour, territoriality, and intra‐guild dynamics. Prey species that rely on habitat structure for avoiding predation often experience increased predation rates and lower survival in recently burnt areas. By contrast, some prey species benefit from the opening up of habitat after fire because it makes it easier to detect predators and to modify their behaviour appropriately. Reduced prey body condition after fire can increase predation risk either through impaired ability to escape predators, or increased need to forage in risky areas due to being energetically stressed. To reduce risk of predation in the post‐fire environment, prey may change their habitat use, increase sheltering behaviour, change their movement behaviour, or use camouflage through cryptic colouring and background matching. Field experiments and population viability modelling show instances where fire either amplifies or does not amplify the impacts of predators on prey populations, and vice versa . In some instances, intense and sustained post‐fire predation may lead to local extinctions of prey populations. Human disruption of fire regimes is impacting faunal communities, with consequences for predator and prey behaviour and population dynamics. Key areas for future research include: capturing data continuously before, during and after fires; teasing out the relative importance of changes in visibility and shelter availability in different contexts; documenting changes in acoustic and olfactory cues for both predators and prey; addressing taxonomic and geographic biases in the literature; and predicting and testing how changes in fire‐regime characteristics reshape predator–prey interactions. Understanding and managing the consequences for predator–prey communities will be critical for effective ecosystem management and species conservation in this era of global change.